Rule based reasoning and case based reasoning techniques for juvenile delinquency legal reasoning model - Syed-Abdullah, Sharifah Lailee; Daniyal, Hidayah; A.Rashid, Rusnadewi; Muhamad Noor, Sarina; Sharif, Noorzila (2015)
The ability to extract and analyse correct precedent cases and court orders is critical because recommending correct court orders is of utmost importance in ensuring that every case is trialed accordingly.Currently, precedent cases and court orders are searched and extracted manually thus, causing backlog in juvenile delinquency trials.This paper discusses the development of a Juvenile Delinquency Legal Reasoning (JDLRes) Model that has the ability to imitate human reasoning in assisting probation officer to recommend court orders for juvenile delinquency cases.Rule-based reasoning (RBR) and case-based reasoning (CBR) are the techniques used to add consistency with flexibility when recommending court orders for new cases.The simulation model was developed to validate JDLRes Model.The comparison results between the model and human expert reveal the existence of generality aspect in the legal domain.Future work requires the study of precedent cases and court orders in different states in Malaysia.